2008
DOI: 10.3354/dao01955
|View full text |Cite
|
Sign up to set email alerts
|

Loose shell syndrome of farmed Penaeus monodon in India is caused by a filterable agent

Abstract: Loose shell syndrome (LSS) of farmed black tiger shrimp Penaeus monodon has been reported from Indian shrimp farms since 1998 and is recognized as a major disease problem causing significant economic loss to the shrimp aquaculture sector. Unlike the rapid mortalities associated with viral pathogens such as white spot syndrome virus and yellow head virus, progression of LSS is gradual, leading to low-level progressive mortalities. The signs of LSS include a flaccid spongy abdomen due to muscular dystrophy, spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…The loose shell syndrome characterized by a flaccid spongy abdomen due to muscular dystrophy, lethargic and flaccid. The exoskeleton forms a sort of loose covering over the abdominal musculature, with a gap between the muscle and shell in P. monodon by [1,2,[8][9][10]. In the present study the same symptoms were found in L. vannamei, where the LSS infected shrimps became sluggish, soft exoskeleton, gab between muscle and shell, pigmented hapatopancreas and microbes fouling on the exoskeleton.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The loose shell syndrome characterized by a flaccid spongy abdomen due to muscular dystrophy, lethargic and flaccid. The exoskeleton forms a sort of loose covering over the abdominal musculature, with a gap between the muscle and shell in P. monodon by [1,2,[8][9][10]. In the present study the same symptoms were found in L. vannamei, where the LSS infected shrimps became sluggish, soft exoskeleton, gab between muscle and shell, pigmented hapatopancreas and microbes fouling on the exoskeleton.…”
Section: Discussionsupporting
confidence: 72%
“…This is due to the poor bottom conditions of the ponds. The affected shrimp has a soft carapace with a gap between the muscle tissue and exoskeleton, shrunken hepatopancreas [1].…”
Section: Introductionmentioning
confidence: 99%
“…LSSD was first reported in India in 1998, and the incidence of this disease has increased every year (Alavandi et al 2007). LSSD was prevalent in Tamil Nadu, Andhra Pradesh, Orissa, Gujarat, Kerala, and west Bengal of India (Alavandi et al 2008;Loka et al 2012). The incidence of LSSD was reported in approximately 14-23% of shrimp farms in Tamil Nadu during -1999(Mayavu et al 2003Alavandi et al 2008) and incurred a loss of ∼9.125 million USD in 2006 (Alavandi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…LSSD was prevalent in Tamil Nadu, Andhra Pradesh, Orissa, Gujarat, Kerala, and west Bengal of India (Alavandi et al 2008;Loka et al 2012). The incidence of LSSD was reported in approximately 14-23% of shrimp farms in Tamil Nadu during -1999(Mayavu et al 2003Alavandi et al 2008) and incurred a loss of ∼9.125 million USD in 2006 (Alavandi et al 2008). Together with the WSSD, LSSD has caused severe economic losses for penaeid shrimp farms in north coastal Andhra Pradesh and east Godavari district in India (Loka et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An abbreviated listing of Shrimp and Prawn viruses: Baculovirus [99a]; Dicistroviruses [100]; Hepatopancreatic parvovirus [99b, 101]; Taura syndrome virus [102][103][104]; Yellow head nidovirus [105]; Gill-associated and yellow head okavirus [106]; Whispovirus. White spot syndrome virus [107][108][109][110]; Loose shell syndrome virus [111]; Crustacean antiviral immunity [112].…”
Section: The Hiding Place Of the Original Cholera Virulence Genesmentioning
confidence: 99%